2003
DOI: 10.1590/s0100-879x2003000500015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute nitric oxide synthase inhibition in the modulation of heart rate in rats

Abstract: Acute nitric oxide synthase inhibition with N G -nitro-L-arginine methyl ester (L-NAME) on chronotropic and pressor responses was studied in anesthetized intact rats and rats submitted to partial and complete autonomic blockade. Blood pressure and heart rate were monitored intra-arterially. Intravenous L-NAME injection (7.5 mg/kg) elicited the same hypertensive response in intact rats and in rats with partial (ganglionic and parasympathetic blockade) and complete autonomic blockade (38 ± 3, 55 ± 6, 54 ± 5, 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 30 publications
7
16
0
Order By: Relevance
“…In fact, it has been observed that in the rat with autonomic-blocked N G -nitro-Larginine methyl-ester (L-NAME) administration induces tachycardia, along with an increase in blood pressure. These effects are partially prevented by thyroidectomy and are not affected by adrenalectomy (Fellet et al, 2003(Fellet et al, , 2004. The tachycardic effects of NO inhibition in this rat model are in contrast to those observed by Ward and Angus (1993) in the rabbit.…”
Section: Nitric Oxide and Heart Ratementioning
confidence: 58%
“…In fact, it has been observed that in the rat with autonomic-blocked N G -nitro-Larginine methyl-ester (L-NAME) administration induces tachycardia, along with an increase in blood pressure. These effects are partially prevented by thyroidectomy and are not affected by adrenalectomy (Fellet et al, 2003(Fellet et al, , 2004. The tachycardic effects of NO inhibition in this rat model are in contrast to those observed by Ward and Angus (1993) in the rabbit.…”
Section: Nitric Oxide and Heart Ratementioning
confidence: 58%
“…The role of NO in the regulation of cardiac function and circulatory system has been remarkably studied in both normal and pathological conditions (Bolli, et al 1998,Fellet, et al 2003,Kojda, et al 1997,Colley and Sivarajan 1984,Crystal, et al 1988). The principal reported effect of NO on cardiac function describes bimodal effects on inotropy with positive inotropic effects at reduced NO availability, and negative inotropic effects at increased NO availability (Kojda, et al 1997,Preckel, et al 1997,Brady, et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of l‐ NAME in isolated atria, in an equivalent dose used in in vivo experiments, did not affect either chronotropic or inotropic effects. Thus, the l‐ NAME‐induced tachycardia, observed in vivo , might not be due to a direct action of the inhibitor on the pacemaker (Fellet et al 2003). Alterations in thyroid and adrenal status, in secretions of vasoactive substances (Nagayama et al 1998; Dillmann, 2002; Lee et al 2002), as well as physical factors such as shear stress might be involved in this positive chronotropic response (Iadecola et al 1994).…”
mentioning
confidence: 99%